Cadmium and Lead in Blood Cockle (Anadara granosa) from Asajaya, Sarawak, Malaysia - Md. Faruk Hossen; Sinin Hamdan; Md. Rezaur Rahman (The Scientific World Journal)
The concentrations were ranged from 1.35±0.16 to 2.22±0.34 µg/g (dry weight) and 2.65±0.34 to 4.36±0.53 µg/g (dry weight) for Cd and Pb, respectively, in blood cockle Anadara granosa from four sites of Sabang River, namely, Kampung Sambir, Kampung Tambirat, Beliong Temple, and Kampung Tanjung Apong, which are located at Asajaya, Sarawak, Malaysia. All values exceeded safety limits set by Malaysian Food Regulation (1985). It may be the cause of serious human health problems after long term consumption. Thus, consumer should have consciousness about such type of seafood from mentioned sites and need further investigation.